2017
DOI: 10.24874/ti.2017.39.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: the Influence of Oil-based Friction Modifier Quantity on Tram Braking Distance and Noise

Abstract: In the present study, the twin disc machine and the light rail system was employed in order to investigate the ability of oil-based friction modifier (FM) to optimize adhesion and to reduce noise. The risks associated with poor adhesion conditions after the application of FM were evaluated. Both laboratory and field experiments showed that if the contact is overdosed by FM, the poor adhesion, which results in the extension of braking distance, can occur. In contrast, the smaller quantities do not cause critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Based on the above-mentioned laboratory experiments [1], TORL-A was chosen as a suitable TOR lubricant for field trials [2] where TOR lubricant was applied using newly developed off-board system. Figure 1b shows the results of braking tests [2] where the effect of applied quantity on the tram braking distance was investigated. It is evident that larger quantities (4 and 2 g/rail) led to the unacceptable long braking distances as a result of contact overdosing, see Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above-mentioned laboratory experiments [1], TORL-A was chosen as a suitable TOR lubricant for field trials [2] where TOR lubricant was applied using newly developed off-board system. Figure 1b shows the results of braking tests [2] where the effect of applied quantity on the tram braking distance was investigated. It is evident that larger quantities (4 and 2 g/rail) led to the unacceptable long braking distances as a result of contact overdosing, see Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
“…The friction creepage curves in Figure 6 are obtained by modifying equations ( 6) and (10). In particular, the friction creepage curve with zero slope is given by Shen et al, 28 which can be expressed as, while the friction creepage curve with positive slope is obtained by modifying the equation ( 10) to,…”
Section: Vibrations Under Non-negative Damping Conditionmentioning
confidence: 99%
“…To sum up, squeal noise should be eliminated when the negative slope is eliminated after the application of FMs according to the negative damping theory, but the results of field trials and laboratory tests of friction modifier have shown that squeal still exists under non-negative damping conditions. 10 A possible reason why squeal noise still exists after the friction curve has been modified to positive might be due to an alternative squeal mechanism known as mode coupling, 11 which is considered to be another possible generation mechanism of curve squeal in addition to the negative damping theory. The results of a 1/4 scale test rig 12 showed that squeal noise still occurs in the case of constant friction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eadie [12,13] states that FMs can reduce wheel squeal noise and flanging noise by 12 dB in various European mass transit systems. In addition to the effect of oil-based FM on noise, Galas [14] monitored the effect on the braking distance of the vehicle. The results showed that it is difficult to reduce the SPL without significantly affecting the braking distance.…”
Section: Introductionmentioning
confidence: 99%